On the Evolution of Interpreting Strategies in Simultaneous Interpreting - Riccardi, Alessandra (Meta, 2005)
AbstractThis paper examines simultaneous interpreting (SI) from the viewpoint of procedural competence, whose evolution may be followed and monitored through the changes intervening within implicit and explicit tasks performed. As a goal-oriented communicative activity, SI may be analysed through the strategies applied to achieve the communicative goal. The interpreter, first during his studies and then throughout his career, develops and constantly refines a strategic behaviour integrating conscious and unconscious strategies. Strategies are a dynamic concept, useful not only for the description of process-oriented aspects of SI, but also as a teaching tool orienting the study and for devising exercises that help automatize specific interpreting solutions.